Pengembangan Motif Daun Pare Sebagai Motif Hias Karya Pintu Kuwadi Di Galih Ukir - I Putu Maha Diadnyana; I Nyoman Dana; Ni Kadek Karuni (Pusat Penerbitan LP2MPP ISI Denpasar, 2022)
This creation was made with the aim of developing one of the decorative styles in Galih Ukir with the title: